2020
DOI: 10.1037/aca0000256
|View full text |Cite
|
Sign up to set email alerts
|

What should people be told when they take a divergent thinking test? A meta-analytic review of explicit instructions for divergent thinking.

Abstract: Divergent thinking (DT) tests are often used for creativity assessment. They differ from many other tests in that they are open-ended. A great deal of research has examined the influence of test instructions on the number and nature of responses to DT tests. Most instructions explicitly emphasize quantity (e.g., "give as many ideas as you can"). Others target additional features, such as creativity, originality, or idea quality. Do such alternative explicit instructions make any difference? The present meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 90 publications
5
60
0
Order By: Relevance
“…When presented with nouns and instructed to "think creatively" while searching for verbs to relate to the nouns, participants produced responses that were significantly more semantically distant, defined as the inverse of semantic similarity, compared to when they were not cued to think creatively (and simply generated common verbs). Here, the simple instruction to "think creatively" yielded more creative (i.e., semantically distant) responses, consistent with prior work showing explicit instruction to think creatively improves creative task performance (Acar, Runco, & Park, 2019;Said-Metwaly, Fernández-Castilla, Kyndt, & Van den Noortgate, 2019). Critically, at the individual subject level, the authors found that semantic distance values in the cued creativity condition correlated positively with a range of established creativity measures, including human ratings of creativity on divergent thinking tests, performance on a creative writing task, and frequency of self-reported creative achievement in the arts and sciences.…”
Section: Automating Creativity Assessmentsupporting
confidence: 86%
“…When presented with nouns and instructed to "think creatively" while searching for verbs to relate to the nouns, participants produced responses that were significantly more semantically distant, defined as the inverse of semantic similarity, compared to when they were not cued to think creatively (and simply generated common verbs). Here, the simple instruction to "think creatively" yielded more creative (i.e., semantically distant) responses, consistent with prior work showing explicit instruction to think creatively improves creative task performance (Acar, Runco, & Park, 2019;Said-Metwaly, Fernández-Castilla, Kyndt, & Van den Noortgate, 2019). Critically, at the individual subject level, the authors found that semantic distance values in the cued creativity condition correlated positively with a range of established creativity measures, including human ratings of creativity on divergent thinking tests, performance on a creative writing task, and frequency of self-reported creative achievement in the arts and sciences.…”
Section: Automating Creativity Assessmentsupporting
confidence: 86%
“…Even though many DT tests traditionally instruct participants to produce many ideas, researchers have begun to modify the instructions to be more specific about the test’s intention to work towards original ideas. For example, Forthmann et al ( 2016 ) found a performance advantage resulting in a higher creative quality of ideational pools when participants were instructed to be-creative , compared to be-fluent instructions, which is in accordance with meta-analytical findings ( Acar et al 2020 ; Said-Metwaly et al 2020 ). The meta-analysis of Kim ( 2005 ) did not differentiate between different settings (game-like vs. test-like), which is considered a limitation.…”
Section: The Relationship Between Intelligence and Dtsupporting
confidence: 82%
“…Instructing participants to be-creative leads to more sophisticated responses, whereas instructing participants to be-fluent influences the number of responses. Hence, researchers get what they ask for ( Acar et al 2020 ). Since DT is considered to be a marker of creative potential ( Runco and Acar 2012 ), the assessment of the originality of the responses seems required (e.g., Zeng et al 2011 ) and, as a matter of fact, is provided in most of the recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have explored these issues indicating promising solutions. First, adding qualitative instruction (e.g., creative) to the traditional quantitative ones results in the generation of more creative and potentially more original ideas (Acar, Runco, & Park, 2020). Secondly, alternative scoring methods, such as the semantic networks approach, have been shown to be highly objective and cost‐efficient methods for quantifying originality and flexibility (Acar & Runco, 2019).…”
Section: Limitations and Conclusionmentioning
confidence: 99%